2015
DOI: 10.1103/physrevb.92.201413
|View full text |Cite
|
Sign up to set email alerts
|

Structural evolution and optoelectronic applications of multilayer silicene

Abstract: Despite the recent progress on two-dimensional multilayer materials (2DMM) with weak interlayer interactions, the investigation on 2DMM with strong interlayer interactions is far from its sufficiency. Here we report on first-principles calculations that clarify the structural evolution and optoelectronic properties of such a 2DMM, multilayer silicene. With our newly developed global optimization algorithm, we discover the existence of rich dynamically stable multilayer silicene phases, the stability of which i… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
22
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(24 citation statements)
references
References 37 publications
2
22
0
Order By: Relevance
“…54 silicene from the monolayer to quadlayer. 113 The most stable bilayer silicene phase is the same as that obtained in previous work. 54,122 For trilayer silicene, the two most stable present a 2 × 1 periodicity with hexagonal and rectangular supercells, which have P121/m1 and P1 symmetries, respectively.…”
Section: Q2d Sisupporting
confidence: 72%
See 1 more Smart Citation
“…54 silicene from the monolayer to quadlayer. 113 The most stable bilayer silicene phase is the same as that obtained in previous work. 54,122 For trilayer silicene, the two most stable present a 2 × 1 periodicity with hexagonal and rectangular supercells, which have P121/m1 and P1 symmetries, respectively.…”
Section: Q2d Sisupporting
confidence: 72%
“…Instead, Luo et al found a new bilayer structure which has a lower total energy than that of AA‐Si by 41 meV/atom . Afterwards, Guo et al performed extensive searches for the most stable phases of silicene from the monolayer to quadlayer . The most stable bilayer silicene phase is the same as that obtained in previous work .…”
Section: Applicationsmentioning
confidence: 73%
“…These considerations find an immediate application in the context of thermometry, since, on the one hand, we assist at the interaction for a given time of a probe with the monitored system, while, on the other, the probe itself needs being prepared in an informative, hence resourceful, state [13][14][15][16][17]. In [18], Jevtic et al have discussed the implementation of an elementary thermometer with a single qubit: the task is not the estimation of arbitrary temperatures, but the discrimination between two thermal baths at different temperatures.…”
mentioning
confidence: 99%
“…In addition, due to the strong covalent bonding character of Si, as-cleaved surfaces inevitably have unpaired electrons localized at dangling bonds on the surface, which makes an energetically unfavorable situation. This is evidenced by prevalent severe surface reconstruction to reduce the number of unpaired electrons as can be seen in most of the previously reported 2D Si crystals [21][22][23][24][25][26][27]33 . In all the cases, however, some of the surface atoms still remain under-coordinated even after the reconstruction, implying that those atoms prone to form strong covalent bonding with one another as pointed out in the case of silicene 1,37 .…”
Section: Introductionmentioning
confidence: 86%
“…1. The surface layer features perfectly planar stable hexagonal framework unlike other 2D Si crystals that have hitherto been studied [21][22][23][24][25][26][27][28][29][30][31][32][33] , in which buckled surfaces are predominant. Moreover, the crystal is completely free from coordination number (CN) defects.…”
Section: Introductionmentioning
confidence: 99%